Metaphyseal dysplasia, Spahr type; missense MMP13 mutations in two Iraqi siblings. Issue 1 (January 2017) - Tadros, Shereen; Scott, Richard H.; Calder, Alistair D.; Hurst, Jane A.
Abstract : We report on two siblings of Iraqi descent with clinical and radiographic features of metaphyseal dysplasia, Spahr type (MDST), born to consanguineous unaffected parents. Molecular testing confirmed pathogenic mutations in MMP13 . We review the considerable overlap between MDST and other related disorders. These cases confirm the phenotypic variability and regressive nature of MDST in addition to suggesting bone fragility as a feature.